Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPS di SD - Sarah S.N Tombokan (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research was conducted in grade IV SD GMIM Wailan. The results of the observation show that when the learning process of Social Sciences (IPS) with material on social problems in the surrounding environment, the final grades achieved by students are not satisfactory or far from expected, where of the 16 students in the class, only 6 people students (37.5%) had reached the KKM (75%), while the other 10 students (62.5%) had not mastered the material or had scores far below the predetermined KKM, namely 75%. This happens because the teacher is less creative in learning or only focuses on the teacher himself, so that students are still mostly playing and making noise in the classroom when teaching and learning activities take place. The research method used was Classroom Action Research (PTK) according to Kemmis and Mac Taggart (Aqib Zainal, 2006) which included the planning stage, the action stage, the observation stage and the reflection stage. This research was conducted in two cycles. The data was collected using direct observation techniques of the learning process and tests. The data obtained from the teaching and learning process were calculated using the KKM formula (Minimum Completeness Criteria). The learning result in cycle 1 is 64.68% and becomes 85.31% in cycle II. So in this study it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve social studies learning outcomes in class IV SD GMIM Wailan. It is recommended that teachers who teach in grade IV SD GMIM Wailan be able to apply the Problem Based Learning (PBL) learning model in the learning process, especially in social studies subjects with material on social problems in the surrounding environment.